Pengaruh Intensitas Menonton Tayangan Sinetron Anak Jalan Pada Perilaku Imitasi Siswa SMP (Faculty of Communications Science, Dr. Soetomo University, 2017)
In the current era of information globalization, Indonesia is enlivened by the presence of several private television stations such as ANTV, INDOSIAR, TRANSTV, MNC TV, RCTI, SCTV, GLOBAL TV, TV ONE, TRANS 7, METRO TV. All of these private televisions are trying to attract as many viewers as possible and can occupy the highest portion. Street children's soap operas that aired on RCTI succeeded in sucking the public's attention, not least the citizens of Surabaya. That's why television is very big influence in changing the behavior of the audience. Imitation is the first level of apparent influence, in which viewers see repeatedly the behavior of their idol figures and tend to mimic those behaviors. This is understandable because one of the developmental behaviors of a person is generated from their more mature examples, parents, family, teachers, even other people who become idols. They often witnessed the soap opera starring Stefan William and Nathasa Wilona whose name is now starting to stick out. The emergence of imitation behavior in adolescents is not